Evaluating some Yule-Walker Methods with the Maximum-Likelihood Estimator for the Spectral ARMA Model - Bezerra, M.I.S.; Iano, Y.; Tarumoto, M.H. (Trends in Computational and Applied Mathematics, 2008)
The aim of this work is to compare some ARMA spectral separatede stimation methods based on the modified Yule-Walker equation and least squares method with the Maximum-Likelihood estimator, using the convergence curve of the relative mean error (RME), generated by Monte Carlo simulation.